Large Sample Neutron Activation Analysis: Developments and Perspectives - Vasilopoulou, T.; Tzika, F.; Stamatelatos, I. E. (HNPS Advances in Nuclear Physics, 2020)
Most of the available analytical techniques do not comply with the need for direct trace element analysis of samples of mass exceeding the order of grams. Instead sub-sampling methods are used to obtain representative sampling of the studied material. Large Sample Neutron Activation Analysis (LSNAA) is a powerful technique, which can fulfill this need in a non-destructive way, free of sample size restrictions due to the high penetrating properties of neutrons and gamma rays in matter. However, corrections are required in order to obtain quantitative analysis results. Due to its distinct advantage to allow for the analysis of whole objects, LSNAA has found successful applications in diverse fields of science and technology. In the present study, the LSNAA method and applications representative of the capabilities of the technique are presented. Moreover, recent developments and future perspectives of the technique are discussed.